The Effect Of Managerial and Institutional Ownership Towards Earnings Management With Profitability As Moderating Variable - agung prayogi; Christina Tri Setyorini (AKUNTANSI DEWANTARA, 2020)
This research aims to predict the effect of managerial ownership and institutional ownership towards earnings management with profitability as moderating variable. The population of this research is 52 consumer goods industrial companies that are listed in Indonesia Stock Exchange year 2016-2018. The sample of this research consists of 18 consumer goods industrial companies which are chosen using purposive sampling method. Technique of data analysis carried out in this research are multiple linear regression analysis and moderated regression analysis. The result of the research states that managerial ownership does not affect negatively towards the earnings management. That is because the managerial ownership is not capable to be the media of the corporate governance which could decrease interest disharmony between management with owner or shareholder. Besides, the percentage of managerial ownership in Indonesia is still low. So does institutional ownership does not negatively affect the earning management. It is because there are many institutions that less active in giving pressure to management activity and lacks of supervision towards the management’s work. Meanwhile, profitability with return on assets proxy is not able to weaken the effect of managerial ownership and institutional ownership towards earnings management. From the result of the research, it can be concluded that companies should increase the implementation of good corporate governance to decrease the practice of earning management. Besides, investors should be careful in their investments activities of a company.